2014
DOI: 10.11002/kjfp.2014.21.4.549
|View full text |Cite
|
Sign up to set email alerts
|

Anti-diabetic effect of the mixture of mulberry leaf and green tea powder in rats with streptozotocin-induced diabetes

Abstract: This study investigated the hypoglycemic effects of mulberry leaf (M), green tea (G), and a mixture of mulberry leaf and green tea (MG) in rats with streptozotocin-induced diabetes. Male Sprague-Dawley rats were divided into the non-diabetic (N) and diabetic groups. The experimental animals were divided into four groups and fed the following for four weeks: a normal diet (N), the STZ+normal diet (STZ), the STZ+5% mulberry leaf (STZ-M), STZ+5% green tea (STZ-G), and the STZ+5% mixture of mulberry leaf and green… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Some studies have reported that the anthocyanin content of mulberry leaves can influence their anti‐diabetic effects (Lee & Hong, 2010). Son et al (2014) reported that mulberry leaves had higher α‐glucosidase inhibitory effects than green tea leaves. Different thermal treatments of mulberry leaves had varied effects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have reported that the anthocyanin content of mulberry leaves can influence their anti‐diabetic effects (Lee & Hong, 2010). Son et al (2014) reported that mulberry leaves had higher α‐glucosidase inhibitory effects than green tea leaves. Different thermal treatments of mulberry leaves had varied effects.…”
Section: Resultsmentioning
confidence: 99%
“…Most previous studies have reported that mulberry leaves have good anti-type II diabetic effects exerted by 1-deoxynojirimycin, 1,4-dideoxy-1,4-imino -D-arabinitol, and 1,4-dideoxy-1,4-imino-D-ribitol compounds that function as α-glycosidase inhibitors with hypoglycemic activities(Kojima et al, 2010). Some studies have reported that the anthocyanin content of mulberry leaves can influence their anti-diabetic effects(Lee & Hong, 2010) Son et al (2014). reported that mulberry leaves had higher α-glucosidase inhibitory effects than green tea leaves.…”
mentioning
confidence: 99%
“…The silkworm has been used as a functional material in the food industry because it has been reported to have various functions such as hepatoprotective effects [13], blood sugar improvement effects [14], gut microbiota composition modulation [15], and antioxidant activity [16]. Mulberry leaves are rich in nutrients and contain high levels of various bioactive substances such as polyphenols and flavonoids [17,18]. The nutritional and functional components of mulberry leaves significantly affect silkworm growth and quality [19].…”
Section: Introductionmentioning
confidence: 99%
“…Morus alba (commonly known as white mulberry) belongs to the family Moraceae, and the mulberry leaves are commonly known to serve as food for silkworms. These leaves are rich in nutrients such as proteins, vitamins, and minerals, contain a large amount of dietary fiber, and have a high content of various bioactive substances such as flavones, steroids, and triterpenes [27,28]. In addition, the nutritional and functional components of mulberry leaves have very important effects on the growth and quality of silkworms [29].…”
Section: Introductionmentioning
confidence: 99%